1963
DOI: 10.1677/joe.0.0260273
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation Between the Content of Vasopressin and Neurosecretory Material in the Rat Neurohypophysis

Abstract: Vasopressin content and the staining of neurosecretory material with chrome-alum-haematoxylin-phloxin were observed in the neurohypophysis of rats following injection of formalin. The amount of neurosecretory material was reduced during the period up to 90 min. after formalin injection while no change in the vasopressin content was observed. These observations support the concept that the neurosecretory material is distinct from vasopressin and may be acting as a carrier or precursor for the hormones of the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1966
1966
1972
1972

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 14 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Scharrer (1952) and Leveque & Scharrer (1953) found that dehydration caused a depletion of the neurosecretory material in the neurohypophysis, that rehydration led to a progressive re-accumulation of this secretory material in the pars neuralis and that an approximately normal amount was noted in animals killed 1 week after rehydration. As reported by Moses, Leveque, Giambattista & Lloyd (1963), however, a correlation between the amount of neurohypophysial hormones and the neurosecretory material in the neurohypophysis was not demon¬ strated in rats subjected to painful stimuli. Therefore, a quantitative study of the repletion of vasopressin and oxytocin in the rat neural lobe was undertaken.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…Scharrer (1952) and Leveque & Scharrer (1953) found that dehydration caused a depletion of the neurosecretory material in the neurohypophysis, that rehydration led to a progressive re-accumulation of this secretory material in the pars neuralis and that an approximately normal amount was noted in animals killed 1 week after rehydration. As reported by Moses, Leveque, Giambattista & Lloyd (1963), however, a correlation between the amount of neurohypophysial hormones and the neurosecretory material in the neurohypophysis was not demon¬ strated in rats subjected to painful stimuli. Therefore, a quantitative study of the repletion of vasopressin and oxytocin in the rat neural lobe was undertaken.…”
Section: Introductionmentioning
confidence: 55%
“…Although Scharrer (1952), in his morphological study, found that it took only 1 week for the depleted neural lobe to resume its normal appearance in respect of neurosecretory material, the stainable material probably is distinct from neuro¬ hypophysial hormones as suggested by the results of Moses et al (1963). Moreover, Daniel & Lederis (1966), who studied electron-dense particles in neurohypophysial nerve fibres of the rat in respect of effects of ether anaesthesia and haemorrhage, have suggested that the quantity of electron-dense material is not related to hormone content.…”
Section: Discussionmentioning
confidence: 98%
“…Based on these reports in nursing as well as in parturient animals, we consider that the disappearance of stainable and osmiophilic material during suckling may reflect an intragranular or axoplasmal reorganization of neuro¬ secretory material (hormone-neurophysin complex) and may be due to changed stainability rather than to a real discharge of this material into the blood stream. Further, the discrepancy between the neural lobe content of hormones and stainable neurosecretory material has previously been pointed out by several authors (Drager & Rennels, 1955; Moses, Leveque, Giambatista & Lloyd, 1963;Daniel & Lederis, 1966). In rats subjected to acute bleeding or strong osmotic stimuli a reduction in radioactivity offraction A was observed (Norström & Sjöstrand, 1971c, 1972.…”
Section: Seriesmentioning
confidence: 93%